Failure mechanism of two-dimensional granular columns: Numerical simulation and experiments - Cuong, Nguyen Tien; Ha, Bui Hong; Fukagawa, Ryoichi (Vietnam Journal of Mechanics, 2015)
In this article, two typical experiments for two types of destruction of granular column were performed by 2D soil model. High speed camera was used to record the movements of the destruction of the granular column. The images clearly showed the whole development of granular flows. The destruction process of the granular column in the two experiments is a big deformation problem of soil mechanics. To simulate the destruction process of the granular column, a model solving the problem of soil mechanics by Smoothed Particle Hydrodynamics (SPH) method was developed. The basic equations of problems of soil mechanics using the Drucker-Prager constitutive model were discretized using SPH method. The calculation results of the numerical model developed by us were compared with the experiment results obtained at the same time since the destruction of the granular column started. This was the first time by comparing and analyzing in details the characteristics of the process of destruction and developments of granular flows for the two typical types of destruction of granular column, it was shown that the numerical model describes quite accurately the characteristics of granular flows in both space and~time.